Social Networks and Cyberbullying at Universidad Veracruzana - Dorantes Carrión, Jeysira Jacqueline (2016)
This paper is part of a research developed at Universidad Veracruzana, in which cyberbullying was studied as a phenomenon practiced among university students through social networks. The main purpose is to show how violent acts such as offenses, intimidation and exhibition are developed inside university areas through the inappropriate use of social networks. These acts harm the society, its individuals, its families, as well as students’ private life, including their future professional life.